THE EFFECT OF IRON POLYMALTOSE COMPLEX TABLET ADMINISTRATION TO INCREASE HEMOGLOBIN LEVEL AMONG PREGNANT WOMEN WITH ANEMIA - Cahyaning Puji Astuti; Melyana Nurul Widyawati; Sri Endang Pujiastuti (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Anemia is a major cause of bleeding due to iron deficiency. Iron tablets which contain 60 mg of Ferrous Sulphate and 0.25 mg of folic acid did not show good results in changing the body’s iron level and there are many perceived side effects. However, there is now exists an oral iron tablets in the form of available salt compounds of ferrous fumarate, ferrous sulphate, and ferrous gluconate. These tablets contain iron hydroxide polymaltose complex (III) or better known as IPC (Iron Polymaltose Complex) and have minimal side effects. Aims: To understand the effect of IPC tablets in increasing the hemoglobin level in pregnant women with anemia. Methods: This study used quantitative study with pre-experimental design, or experiments that have not been applied in real terms. This study used non-probability sampling technique and purposive sampling for the selected sample. The sample were 35 people based on the inclusion criteria. The design used was one group pre-test – post-test approach without the control group. The subjects undertook the anemia examination on the first day (pre-test) and afterwards were administered 100mg IPC tablets daily for the next 30 days. In the end of the intervention, the subjects were re-examined and the results were compared (post-test). Results: The study showed that there is a significant increase of hemoglobin level in pregnant women with anemia with p value = 0.023 (p<0.05) after the intervention in the form of IPC tablet administration was conducted for 30 days. Conclusion: The intervention performed in administration of IPC tablets for pregnant women with anemia showed a significant increase of hemoglobin level before and after the provision of IPC tablets.